Gênero e a formação de psicólogas/os em Goiás: problematizando (in)visibilidades e reflexos no ensino acadêmico - Assis, Marcelo Marques (2018)
In this study, we investigated how gender discourses are part of the process in Psychology formation, in Goiânia / GO. We assume gender as an element that constitutes and organizes social relations, through discursive practices that interrelate in a historical, social, cultural and political moment. We recognize formation as processes that consider human being as subject of their own development, built from social relations. It is a qualitative research, theoretically at the interface between gender studies and feminist epistemologies, linked to post structuralism. In order to reach our objectives, we conducted a documentary research and a field research, carried out in two higher education institutions in Goiânia. The National Curricular Guidelines (DCN) composed the corpus of documentary research for Psychology Courses and Pedagogical Projects of Psychology Courses (PPC) of the studied institutions, and field research, developed from semi-structured interviews with five teachers from Núcleo Docente Estruturante (NDE) courses. We adopted the Discourse Analysis to verify the information constructed in the research. Documentary research results evidenced gender discourses invisibility in the DCN and their little presence in the PPCs of both institutions studied. In the field research, the participants recognized the importance of inserting gender studies in psychology training, emphasizing the need for the courses to promote, either in a specific discipline or in a transversal way to other disciplines, spaces that contemplate discussions on the subject, seen as part of psychologists skills and abilities. We hope that this research contributes to training projects development in psychology, committed to overcoming psychological practices that (re) produce pathologization, oppression and gender discrimination. It is necessary that psychologists become agents engaged in society transformation policies, among which we highlight gender issues.